Efforts To Improve The Learning Activity And Learning Outcomes Of Physics Students With Using A Problem-Based Learning Model - Kawuri, Maria Yosephien Retna Tinon; Ishafit, Ishafit; Fayanto, Suritno (IJIS Edu : Indonesian Journal of Integrated Science Education, 2019)
The goal of this investigation to implement a problem-based learning model as an effort to improve student learning activities and outcomes. This model of research is a classroom action research divided into two cycles. The study conducted at High School 1 Piyungan class X MIPA 1 totaling 35 students consisting of 15 male and 20 female, the topic used the momentum and impulse of semester 2. The research instrument is observation sheet, achievement test, and questionnaire. The results of the analysis learning model with problem-based learning can increase the activity of studying physics class X MIPA1. Improved physics learning activities of class X MIPA 1 students at High School 1 Piyungan with problem-based learning for the academic year 2018/2019 from the first cycle at the first meeting and the second meeting increased from 84.75% to 91.11% which was 6.36In the second cycle there was an increase from 85.28% to 91.85%, an increase of 6, 57%.